Hubungan Antara Kontrol Diri Dan Keterampilan Sosial Dengan Kecanduan Internet Pada Siswa SMK - Istri, Dwi; , Setia Asyanti S.Psi, M.Si (2016)
Internet addiction is a behavioral pattern of excessive Internet use is causing people restrict their social activities because the individual assumes that the Internet more interesting and fun than the real world. Internet addiction is influenced by several factors including self-control and social skills. The purposes of this study were to determine the relationship between self-control with Internet addiction in students of SMK; and the relationship between social skills with Internet addiction in students of SMK. This research was conducted at SMK X Klaten. This research was conducted at SMK X Klaten. Subjects in this study were students of SMK X Klaten class X and XI which totaled 126 students (M = 124, F = 2) were aged 14-18 years and taken with quota sampling technique. Measuring instrument used is the Internet addiction scale, the scale of self-control and social skills scale. Data were analyzed using multiple regression analysis. The results were obtained (a) There is a significant negative relationship between self-control with internet addiction with values (r = -0.543, p = 0.000); (b) There is a significant negative relationship between social skills with internet addiction (r = -0.486, p = 0.000). (c) Self-control and social skills contribute to Internet addiction by 34.7%. Variables internet addiction and self-control are included in the category of low and social skills included in the medium category. These results imply that the importance of self-control and social skills against internet addiction. The results will be discussed in the text of this publication.